The labourers and the great agrarian property in the South of Spain - Martín Martín, Víctor O. (Anales de Geografía de la Universidad Complutense, 2008)
The following lines form a part of a project of research that tries to answer to the question of the title of this article: does it continue hanging the agrarian question in the South of Spain? We do a synthetic tour - across slant of the works of different social sciences, fieldwork and interviews labourers - of the recent history of Andalusia and Extremadura. The objective, first, is to propose an alternative interpretation to the officially admitted: the victory of the agrarian capitalism in the field of these regions. The above mentioned proposed reintepretation there bases on the permanency or stability of the reasons of the secular underdevelopment of the field Extremaduran - Andalusian (permanency of the great property and of the social group of the labourers). Secondly, we raise that the overcoming of the underdevelopment of the South of Spain, in the light of the interpretation suggested in this text, should take the democratization of the land as a solution, the distribution and the agrarian reform in the regions of Andalusia and Extremadura. Les lignes suivantes font partie d’un projet d’investigation plus ample qu’il essaie de répondre à la question: suit-elle pendant la question de la terre au Sud de l’Espagne ? Pour cet article en somme, un parcours synthétique est fait, à travers des travaux de différents scientifiques sociaux, le travail de champ et les entrevues aux journaliers, par les deux derniers siècles de l’histoire agraire récente de l’Andalousie et de l’Estrémadure, avec, en premier lieu, le but de proposer une interprétation alternative à officiellement admise qu’elle projète le triomphe du capitalisme agraire dans le domaine de ces régions. La dite interprétation proposée se base sur la permanence ou la stabilité des causes du "retard" ou le sous-développement séculier du champ d’Estrémadure - Andalou (permanence de la grande propriété et du groupe social des journaliers), et a pour un fil conducteur le concept de semifeudalidad. En deuxième lieu, nous projetons que, à la lumière de l’interprétation suggérée dans ce texte, le dépassement du "retard" du Sud de l’Espagne devrait avoir pour solution la démocratisation de la terre, de la distribution et de la réforme agraire dans les régions de l’Andalousie et de l’Estrémadure.